Eppur Si Muove: Evidence for an External Granular Layer and Possibly Transit Amplification in the Teleostean Cerebellum - Biechl, Daniela; Dorigo, Alessandro; Köster, Reinhard W.; Grothe, Benedikt; Wullimann, Mario F. (Frontiers in Neuroanatomy, 2016)
The secreted signalling factor Sonic Hedgehog (Shh) acts in the floor plate of the developing vertebrate CNS to promote motoneuron development. In addition, shh has dorsal expression domains in the amniote alar plate (i.e. in isocortex, superior colliculus and cerebellum). For example, shh expressing Purkinje cells act in transit amplification of external granular layer cells of the developing cerebellum. Our previous studies had indicated the presence of an external granular layer in anamniote zebrafish, but a possible role of shh in the zebrafish cerebellar plate remained elusive. Therefore, we used an existing zebrafish transgenic line Tg(2.4shha-ABC-GFP)sb15; Shkumatava et al 2004) to show this gene activity and its cellular localization in the larval zebrafish brain. Clearly, GFP expressing cells occur in larval alar zebrafish brain domains, i.e. optic tectum and cerebellum. Analysis of critical cerebellar cell markers on this transgenic background and a PH3 assay for mitotic cells reveals that Purkinje cells and eurydendroid cells are completely non-overlapping postmitotic cell populations. Furthermore, shh-GFP cells never express Zebrin II or parvalbumin, nor calretinin.They are thus neither Purkinje cells nor calretinin positive migrating rhombic lip derived cells. The shh-GFP cells also never correspond to PH3 positive cells of the ventral cerebellar proliferative zone or the upper rhombic lip-derived external granular layer. From this marker analysis and the location of shh-GFP cells sandwiched between calretinin positive rhombic lip derived cells and parvalbumin positive Purkinje cells, we conclude that shh-GFP expressing cells qualify as previously reported olig2 positive eurydendroid cells, which are homologous to the amniote deep cerebellar nuclei. We confirm this using double transgenic progeny of shh-GFP and olig2-dsRed zebrafish. Thus, these zebrafish eurydendroid cells may have the same role in transit amplification as Purkinje cells do in amniotes.